Parents' Methods for Instilling Religious Values in Children in Dusun Bulak Monga, Kecamatan Sikakap, Kabupaten Kepulauan - Marnise S, Rinauwati; Suryadi, Suryadi; Adison, Joni (Holistic Science, 2024)
Parental method is a well-organized method used by parents in carrying the burden of responsibility for their children's future seen by instilling healthy beliefs, practicing worship, teaching children the good and bad, getting children used to learning, and give punishment. Parents, consisting of fathers and mothers, have a great responsibility in raising their children, especially in instilling religious values. This research was motivated by the existence of parents who experienced problems in instilling religious values in their children in Bulak Monga Hamlet, Sikakap District, Mentawai Islands Regency. The aim of this research is to describe: Parents' methods of instilling religious values in children. This research was conducted using quantitative descriptive methods. The research population was 30 parents (fathers and mothers) as a sample of the entire population using total sampling techniques. The instrument used is a questionnaire. Meanwhile, for data analysis, interval scores are used. The results of this research reveal that: Parents' methods of instilling religious values in children are in the quite good category, namely 40.0%. Based on the research results, it is recommended that parents increase their knowledge and be aware of their responsibilities in developing religious values in children.